Sustainable Stock Investing: An Exploration of Millennials and Zoomer Investment Behavior and Intentions in ESG Based Corporate Stock Funds and Indexes - Prasetiyo, Yudhi; Wisnantiasri, Sila Ninin; Pradana, Novta Winkey; Andriyansah; Kasmiarno, Kurnia Sari (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study investigates the drivers of ESG-based investment intentions among Millennials and Gen Z in Indonesia. By extending the Theory of Planned Behavior (TPB) to incorporate financial and pro-social dimensions, the research examines a comprehensive set of antecedents, including subjective norms, environmental knowledge, financial literacy, and perceived risk. Adopting a quantitative explanatory design, data were gathered from young investors across major urban centers, including Jakarta, Bandung, Surabaya, and Denpasar. The conceptual model was empirically tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM), chosen for its robust predictive capabilities with complex latent constructs. The findings demonstrate that Subjective Norms, Pro-Social Attitudes, and Perceived Financial Risk are significant predictors of ESG investment intention, which subsequently exerts a strong influence on actual investment behavior. Interestingly, traditional TPB components such as Attitude and Perceived Behavioral Control, along with Financial Literacy and Environmental Knowledge, did not yield significant effects. These results highlight that for Indonesian youth, social influence and ethical values outweigh technical expertise when navigating sustainable investment decisions.